2023
DOI: 10.3389/fpsyg.2023.1137047
|View full text |Cite
|
Sign up to set email alerts
|

Pickleball and mental health in adults: A systematic review

Abstract: IntroductionPhysical activity has been extensively studied and numerous mental health benefits have been found. Pickleball is an emerging racquet sport, which is characterized by its accessibility to all audiences and has become especially popular in the United States among the elderly. It is a novel team game and its inclusive nature is innovative for health improvement. The purpose of this systematic review was to review and evaluate existing studies that have examined the effects of pickleball on the mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…In an analysis of papers relating to pickleball, it was reported that the vast majority of pickleball players were >50 years of age, and pickleball participation resulted in improvements in a sense of personal well-being, reduction of stress and depression, and enhanced satisfaction with everyday life [ 4 ]. The inclusive nature of pickleball makes it a particularly appealing sport for older people.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In an analysis of papers relating to pickleball, it was reported that the vast majority of pickleball players were >50 years of age, and pickleball participation resulted in improvements in a sense of personal well-being, reduction of stress and depression, and enhanced satisfaction with everyday life [ 4 ]. The inclusive nature of pickleball makes it a particularly appealing sport for older people.…”
Section: Reviewmentioning
confidence: 99%
“…The inclusive nature of pickleball makes it a particularly appealing sport for older people. Physical exercise can be an important component of overall health in general and mental health in particular and can be particularly beneficial in people with mental health disorders or physical limitations that might preclude them from other forms of sports [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations